Classics and moderns in economics : essays on nineteenth and twentieth century economic thought - Groenewegen, Peter D. (London ; New York : Routledge, 2003)
Peter Groenewegen's reputation as a Chronicler of the history of economics is unparalleled. Building on his respected collection on eighteenth century economics, these volumes focus on the nineteenth and early twentieth centuries, reprinting essays on classical and modern economics. Several essays have never been previously published while many are difficult to access having been written across the 1970s, 1980s and 1990s. Thety are invaluable resources for historians, students and academics involved in the history of economics
Includes bibliographical references and index.
oif 31/01/2014
Loans
Keywords: Economics